Stochastic Resonance, Self-Organization and Information Dynamics in Multistable Systems - Grégoire Nicolis; Catherine Nicolis (Entropy, 2016)
A class of complex self-organizing systems subjected to fluctuations of environmental or intrinsic origin and to nonequilibrium constraints in the form of an external periodic forcing is analyzed from the standpoint of information theory. Conditions under which the response of information entropy and related quantities to the nonequilibrium constraint can be optimized via a stochastic resonance-type mechanism are identified, and the role of key parameters is assessed.